Osimertinib in advanced EGFR-mutant lung adenocarcinoma with asymptomatic brain metastases: an open-label, 3-arm, phase II pilot study. Issue 1 (27th December 2021) - Peled, Nir; Kian, Waleed; Inbar, Edna; Goldstein, Iris M; Zemel, Melanie; Rotem, Ofer; Rozenblum, Anna B; Nechushtan, Hovav; Dudnik, Elizabeth; Levin, Daniel; Zer, Alona; Keren-Rosenberg, Shoshana; et al.
Abstract: Background: Osimertinib is selective for both epidermal growth factor receptor (EGFR)-tyrosine-kinase inhibitor (TKI) sensitizing and Thr790Met mutations. While intracranial activity of osimertinib is documented in larger trials, a prospective study focusing exclusively on patients with asymptomatic brain metastases has not been reported. Methods: In this nonrandomized, phase II, open-label, 3-arm prospective proof-of-concept pilot study, 48 patients with metastatic EGFR-mutant lung adenocarcinoma (LUAD) received osimertinib 80 mg daily. Patients were either treatment naive (arm A = 20) or previously treated with an EGFR-TKI and Thr790Met positive (arm B = 18) or negative (arm C = 10). In cases of isolated intracranial progression, osimertinib dose was escalated (160 mg). The primary endpoints were intracranial objective response rate (iORR) and intracranial disease control rate (iDCR). The secondary endpoint was intracranial progression-free survival (iPFS). This study is registered at Clinicaltrials.gov, NCT02736513. Results: The iORRs were 84.2%, 66.7%, and 50% and the iDCRs were 94.7%, 94.4%, and 80% in arms A, B, and C, respectively. The median iPFS was 11.8 months (95% CI 7.7 to NA), 7.6 months (95% CI 5.3 to NA), and 6.3 months (95% CI 3.9 to NA) in arms A, B, and C, respectively. Following dose escalation, pooled iORR was 54% (arm A = 5, arm B = 4, arm C = 2). Adverse events were similar to those in previously published literature. Conclusion: Osimertinib demonstrated high efficacy on brain metastases. All trial arms displayed a significant decrease in the number and diameter of target lesions. These findings indicate that osimertinib is effective for Thr790Met-positive and -negative LUAD patients with asymptomatic brain metastases. Therefore, osimertinib should be considered a viable option for EGFR-mutant patients with brain involvement regardless of their Thr790Met mutation status.